2011
DOI: 10.1051/0004-6361/201016303
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic inferences on red giants in open clusters NGC 6791, NGC 6819, and NGC 6811 usingKepler

Abstract: Context. Four open clusters are present in the Kepler field of view and timeseries of nearly a year in length are now available. These timeseries allow us to derive asteroseismic global oscillation parameters of red-giant stars in the three open clusters NGC 6791, NGC 6819 and NGC 6811. From these parameters and effective temperatures, we derive masses, radii and luminosities for the clusters as well as field red giants. Aims. We study the influence of evolution and metallicity on the observed red-giant popula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 56 publications
2
66
0
Order By: Relevance
“…The peak in the mass distribution for NGC 6819 in Fig. 2 in Hekker et al (2011a) is also located at a mass close to 1.5 M . This is significantly less than the mass 1.68 ± 0.03 M derived for RG stars in NGC 6819 by Basu et al (2011) using asteroseismic grid modelling with Kepler light curves.…”
Section: Discussionmentioning
confidence: 93%
“…The peak in the mass distribution for NGC 6819 in Fig. 2 in Hekker et al (2011a) is also located at a mass close to 1.5 M . This is significantly less than the mass 1.68 ± 0.03 M derived for RG stars in NGC 6819 by Basu et al (2011) using asteroseismic grid modelling with Kepler light curves.…”
Section: Discussionmentioning
confidence: 93%
“…This involves exploiting the correlation between the asteroseismic observables and apparent magnitude for stars with very similar mass and effective temperature. The asteroseismology of seven stars (one early AGB and six red clump) have been discussed by different authors (Stello et al 2011a,b;Hekker et al 2011;Corsaro et al 2012), but we have redone the asteroseismic analysis of the nine NGC 6811 candidates using all available long-cadence data from Kepler (starting with either quarters 0 or 1 and reaching quarter 17) in Data Release 23. The longer time baseline compared to previous studies has allowed us to reduce the previously determined uncertainties on the asteroseismic parameters ∆ν and ν max by almost a factor of 1.5 − 2 relative to Corsaro et al (2012).…”
Section: Red Clump Stars and Asteroseismologymentioning
confidence: 99%
“…The brightest stars of the open cluster NGC 6811 comprise a rich set of objects with astrophysical information that has not yet been fully exploited. On the cool side, there are a group of helium-burning red clump and asymptotic giant stars with solar-like oscillations previously detected with the Kepler spacecraft (Stello et al 2011a,b;Hekker et al 2011;Corsaro et al 2012). On the hot side, the bright end of the main sequence fits neatly within the instability strip, and δ Scuti (Sct) and γ Doradus (Dor) pulsating stars have been previously identified (van Cauteren et al 2005;Luo et al 2009;Debosscher et al 2011;Uytterhoeven et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This has the potential to strengthen the procedure followed in this paper. Furthermore, NGC 6791 is in the Field-OfView of the NASA Kepler mission (Borucki et al 2010), which will not only allow many more detached eclipsing binaries to be found and measured, but also complementary model constraints from asteroseismology of the giant stars in the cluster Hekker et al 2011;Pablo et al 2011;Stello et al 2011;Corsaro et al 2012;Miglio et al 2012). All our acceptable model fits give a mass on the RGB at the V-magnitude of the RC in the range 1.15 ± 0.02 M which will be an important consistency check, along with the age and helium content, for future detailed asteroseismic modelling of the cluster giants.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%